Alih Kode dalam Film Meitantei Katherine - Ari Febriantari, Putu; Budiana, I Made; Luhur Wedayanti, Ni Putu (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2021)
This research titled is “Code Switching of Meitantei Katherine Movie”. This research aims to give information about types and causes of Code Switching in Meitantei Katherine movie. The data consists of two different languages, Japanese and English. The method of this reaserch is “padan intralingual” method and informal technique . The theories used are code witching by Romaine (1995), code switching by Wardhaugh (2006), cause code switching by Hoffman (1991) and semiotics by Danesi (2011). Based on the analysis, there are 21 code switching data consisting of one Tag Code Switching, five Intrasentential Code Switching, four Intersentential Code Switching, three Metaphorical Code Switching, and four Situational Code Switching.The Causes of code switching found on analysis are 1) talking about a particular topic; 2) being emphatic about something; 3) interjection; 4) repetition used for clarification; and 5) intention of clarifying the speech content for interlocutor.